Beneficial Effect of Morin on Lipid Peroxidation and Antioxidant Status in Rats with Ethanol Induced Dyslipidemia and Liver Injury - Saravanan, Nadanam (International Journal of Pharmaceutical & Biological Archive, 2013)
Beneficial Effect of Morin on Lipid Peroxidation and Antioxidant Status in Rats with Ethanol Induced Dyslipidemia and Liver Injury